Evolution of drug-resistance genes in Plasmodium falciparum in an area of seasonal malaria transmission in Eastern Sudan. - Abdel-Muhsin, A; Mackinnon, M; Ali, E; Nassir, E; Suleiman, S; Ahmed, S; Walliker, D; Babiker, H (2004)
We investigated the evolution of drug-resistant Plasmodium falciparum in a village in eastern Sudan. The frequencies of alleles of 4 genes thought to be determinants of drug resistance were monitored from 1990 through 2001. Changes in frequencies of drug-resistance genes between wet and dry seasons were monitored from 1998 through 2000. Parasites were also typed for 3 putatively neutral microsatellite loci. No significant variation in frequencies was observed for the microsatellite loci over the whole study period or between seasons. However, genes involved in resistance to chloroquine showed consistent, significant increases in frequencies over time (rate of annual increase, 0.027/year for pfcrt and 0.018/year for pfmdr1). Genes involved in resistance to the second-line drug used in the area (Fansidar) remained at low frequencies between 1990 and 1993 but increased dramatically between 1998 and 2000, which is consistent with the advent of Fansidar usage during this period. For mutant alleles of the primary drug-resistance targets for chloroquine and pyrimethamine, higher frequencies were seen during the dry season than during the wet season. This cyclical fluctuation in drug-resistance genes most likely reflects seasonal variation in drug pressure and differences in the fitness of resistant and sensitive parasites.